Optimizing Reading Instruction through Flexible Grouping Practices - Dhakal, Basanta Raj (KMC Journal, 2025)
This study investigated the teachers’ perceptions and effectiveness of various grouping practices in reading instruction within school classrooms. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews and document analysis with three participating school teachers. These multi methods not only enrich the data but also strengthen the trustworthiness and credibility of findings to explore complex phenomena of grouping providing depth, contextual understanding and systematic data collection. Thematic analysis, involving coding, categorizing and identifying themes, was used to analyze the data. The study revealed key insights regarding the implementation and perceived effectiveness of grouping including increased student engagement, targeted skill development and opportunities for collaboration. However, challenges were also identified, such as time constraints, the need for adapting instruction within groups and managing student behaviour during group work. Therefore, careful planning and implementation are crucial to address potential challenges. Further research can provide educators with a more comprehensive understanding of the potential and limitations of flexible grouping in fostering successful reading development.